(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the prevalence of osteoporosis among postmenopausal women aged 45 years and older in Bao Loc City, Lam Dong Province in 2023 and identify some related factors. Methods: A cross-sectional descriptive study was conducted from June 2022 to June 2023 on 303 postmenopausal women aged 45 years and older in Bao Loc city, Lam Dong province. Results: The prevalence of osteoporosis among postmenopausal women aged 45 years and older in Bao Loc city, Lam Dong province in 2023 was 13.5%. Factors significantly associated with osteoporosis included age, tea-drinking habits, and physical activity levels. Conclusion: Community-based studies assessing osteoporosis prevalence should be expanded, particularly targeting postmenopausal women aged 45 years and older, to enable early detection and preventive measures against osteoporosis-related complications.